Development of an intervention for the social reintegration of adolescents and young adults affected by cancer - Marie Broholm-Jørgensen; Tine Tjørnhøj-Thomsen; Pia Vivian Pedersen (BMC, 2022)
Abstract Background In Denmark, around 500 adolescents and young adults (AYAs) aged 15-29 are diagnosed with cancer each year. AYAs affected by cancer constitute a vulnerable group in need of special support in pursuing everyday life as young people. These needs are, however, not currently being adequately met. This study explores the distinctive needs of AYAs aged 15-25 and affected by cancer with the aim of developing and designing an intervention that accommodates these needs and allows AYAs to pursue everyday life following active cancer treatment. Methods We combined multiple qualitative methods to conduct six sub-studies: 1) participant observation among support groups for AYAs affected by cancer, 2) field visit at a large Danish hospital, 3) qualitative interviews with AYAs currently or previously diagnosed with cancer, 4) qualitative interviews with practitioners working with young cancer patients or AYAs with chronic conditions, 5) an interactive workshop with practitioners, and 6) an interactive workshop with AYAs. The empirical material was collected between May 2016 and April 2019. The empirical material was read, analysed thematically and coded into the themes; 1) diagnosis and treatment, 2) form of education and 3) age, financial challenges and legal entitlements. Results Across the empirical material, we found that AYAs' cancer experience was heterogeneous. The needs of AYAs differed according to 1) diagnosis and treatment, 2) type of education and 3) age, financial situation and legal entitlements. The findings demonstrate a need for a tailored intervention accommodating the variety of opportunities, requirements and challenges of AYAs with cancer. We propose an intervention consisting of a multidisciplinary team sited at the hospital where the individual AYA receives treatment. The team's main task will be to maintain AYAs' social competences and ease their return to everyday life after serious illness by balancing educational requirements with cancer treatment. Conclusion Based on the perspectives of practitioners and AYAs affected by cancer, this study outlines an intervention designed as a care pathway in which a multidisciplinary team provides individual and tailored support to AYAs with cancer from the time of diagnosis during and beyond active cancer treatment.